EVALUATION OF PROPHYLACTIC ANTIBIOTIC USE IN CESAREAN SECTION PATIENTS AT “X” REGIONAL HOSPITAL, SEMARANG REGENCY - lisaIstikhomah; Nisa Febrinasari; Susilowati, Dwi Retna (SAINS INDONESIANA, 2025)
Cesarean section is a surgical procedure performed to deliver a baby by making an incision through the mother’s abdominal wall and uterus. As with any surgical intervention, it carries a risk of Surgical Site Infection (SSI). Prevention of SSI can be achieved through the administration of prophylactic antibiotics, which should be given prior to surgery, particularly in clean and clean-contaminated procedures. From an Islamic perspective, as mentioned in Surah Al-Qamar (verse 49), everything should be in accordance with a set measure. Therefore, this study aims to evaluate the appropriateness of prophylactic antibiotic use based on established clinical guidelines. This study employed a descriptive design with data collected retrospectively. The data consisted of medical records of patients who underwent cesarean section at “X” Regional General Hospital in Semarang Regency. The collected data were then compared with the standards outlined in the Indonesian Ministry of Health Regulation No. 28 of 2021. The findings showed that 52.46% of the prophylactic antibiotics used were in accordance with the guidelines, while 47.54% were not. In terms of dosage, 52.46% of Cefazolin 2 grams administrations were appropriate, while 47.54% of Metronidazole 500 mg administrations were deemed inappropriate. However, the timing of antibiotic administration was found to be 100% appropriate across all cases.